Light Propagation Into, Out of, and Through Mid-Infrared Optical Fibers - Weiblen, Robert Joseph (My University, 2015)
This dissertations studies the theory of mid-infrared (mid-IR) light (~1-10 µm) transmission into, out of, and through mid-infrared optical fibers. This work is broadly comprised of three separate topics - mid-IR supercontinuum generation in chalcogenide photonic crystal fibers (PCFs), moth-eye anti-reflective (AR) microstructures for mid-IR fibers, and negative curvature fibers for broadband mid-IR transmission. Mid-IR radiation has a number of military, biomedical, chemical sensing, and industrial applications that often require high power and broad bandwidth. Consequently, the generation of this broad bandwidth (using supercontinuum generation), its efficient coupling to waveguides (using motheye structures), and low-loss transmission (using antiresonant fibers) are of important practical interest. This work has been carried out in collaboration with an experimental group from the Naval Research Laboratory (NRL) specializing in mid-IR optics and chalcogenide glasses. Supercontinuum (SC) generation is a complex nonlinear process that uses highly nonlinear optical fibers to broaden the bandwidth of a narrow-band input laser source. We extended earlier work in arsenic selenide (As₂S₃) PCFs to arsenic sulfide (As₂S₃) and optimized the input parameters to maximize the output bandwidth as we changed the input pulse peak power and pulse duration. We noticed that the output bandwidth was extremely sensitive to small changes in the input parameters. However, this sensitivity is not visible in experiments due to pulse averaging. We then employed several simulation methods short of large-scale ensemble averaging to reduce the uncertainty in the output bandwidth. The use of these methods offered only a slight reduction in the uncertainty of the output bandwidth; so, we next undertook a large study to completely characterize the statistics of the output spectrum from a supercontinuum source and to definitively determine the output spectrum and corresponding bandwidth that might be observed in an actual experiment. We used a large-scale ensemble average and determined the approximate number of realizations necessary to obtain a converged bandwidth and spectrum. Moth-eye structures are a biomimetic anti-reflective microstructure that can be etched, milled, grown, stamped, or otherwise imprinted onto optical surfaces to reduce Fresnel reflections. We validated several simulation methods by matching the experimentally-recorded transmission spectrum of a particular moth-eye structure. Using these methods, we investigated the effect of changing the shape, size, and period of a moth-eye structure on its transmission spectrum in the region of 2-5 µm. We used this knowledge to design optimal moth-eye structures that had greater than 99% transmission in this wavelength range. We also investigated localized field enhancement effects in moth-eye structures to determine the reason for their high laser-induced damage threshold. We found that localized field enhancement occurs mostly in the air, rather than in the glass, allowing moth-eye structures to melt before suffering catastrophic damage at nearly the same levels as untreated glass. Antiresonant fibers (ARF) are a novel type of hollow-core optical fiber that guide light in an air core by the convex curvature of the core wall. Previous work by others on ARFs have focused on silica, but a design based on chalcogenide glasses such as As₂S₃ will have much lower loss in the mid-IR. We investigate and optimize the size of the core and other dimensions of the fiber to minimize the fiber loss in the range of 1-10 µm. We also study the effect of imperfect fabrication of As₂S₃ ARFs.
Keywords: Antiresonant fibers; Mid-infrared; Motheye structures; Optical fibers; Supercontinuum generation